Impact of Personality and Psychopathy on Deviant Workplace Behaviour: Systemic Approach - Khawaja Sarwar; Sokić Katarina; Qureshi Fayyaz Hussain; Miloloža Ivan (Business Systems Research, 2025)
The main aim of this study was to examine the effect of the HEXACO domains and triarchic psychopathy dimensions on interpersonal and organisational deviant workplace behaviour.